2007
DOI: 10.1167/iovs.06-1315
|View full text |Cite
|
Sign up to set email alerts
|

Optic Disc Measurements in Myopia with Optical Coherence Tomography and Confocal Scanning Laser Ophthalmoscopy

Abstract: While optic disc area generally increased with the axial length and myopic refraction, the HRT measurements demonstrated that optic disc size was largely independent of axial length and refractive error between -8 and +4 D. OCT may overestimate optic disc size in myopic eyes and results in poor agreement between the two instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
109
2
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(123 citation statements)
references
References 25 publications
7
109
2
5
Order By: Relevance
“…The relationship between the measured size of the OCT image and the actual fundus size imaged was also described using Littmann's formula. 20 The main finding of that study was that the optic disc area increases with axial length and myopic refraction. For each millimeter increase in axial length, the optic disc area increased by 0.095 mm 2 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The relationship between the measured size of the OCT image and the actual fundus size imaged was also described using Littmann's formula. 20 The main finding of that study was that the optic disc area increases with axial length and myopic refraction. For each millimeter increase in axial length, the optic disc area increased by 0.095 mm 2 .…”
Section: Discussionmentioning
confidence: 92%
“…10 Similarly, measurement of the optic disc size has an important bearing on the evaluation of optic nerve diseases and anomalies. Leung et al 20 used a Stratus OCT instrument to evaluate associations between optic disc area and axial length/spherical equivalent. The relationship between the measured size of the OCT image and the actual fundus size imaged was also described using Littmann's formula.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20] Thus, the formula for disc area correction was as follows: corrected disc area ¼ 3:382 2 3 0:01306 2 3ðAL À 1:82Þ 2 3ðcomputed SD À OCT disc areaÞ:…”
Section: Estimation Of Dh Areamentioning
confidence: 99%
“…This could be explained by the possibility that small disc area was related to long AL and myopia because OCT might have methodological artifacts. Some investigators have reported that AL might contribute in part to smaller disc area in myopic eyes when the magnification effect was not corrected in OCT. 33,34 Because this study also did not adjust the magnification effect, long AL might make disc size appear small on OCT. However, Kim et al 35 did not find significant correlation between AL and small disc using SD-OCT in their study, and the specific characteristics of cluster 3 were not only long AL and myopia but also younger age, compared with the other groups.…”
Section: Discussionmentioning
confidence: 98%